Collaboration in Cyber Transportation Logistics: Paradigms and Technologies - Toh, Albert K; Chan, Yupo (International journal of applied logistics, 2010)
Although the topic of supply chain (SC) and logistics (L) has been discussed in many fora, placing it in today’s cyber (e) space is still a subject that receives little attention. This paper analyzes the role of e-SC/L in the context of global business to business (B2B) electronic commerce (e-commerce). A major beneficiary of e-SC/L are small and medium enterprises (SMEs), who can leverage information technology to bypass the extra cost associated with employing a third-party broker, who traditionally bridges the gap between suppliers and retailers. In this paper, a framework for incorporating both e-commerce and e-SC/L for SMEs is proposed in an e-marketplace context. The model consists of a trading platform with e-SC/L capabilities, and a classification scheme for different levels e-SC/L collaboration, presented with relevant types of information, communication and transportation technology (ICTT) needed to facilitate the design of each collaboration level. Included in the highest level are transportation, identification, and modeling and simulation technologies that enable the design of effective forward-looking collaboration.